Synthesis of Esters with Different Flavors using Fisher Esterification - Fathia Altalhi,; Hameda Algalbati,; Abdunnaser Magrahi, (AlQalam Journal of Medical and Applied Sciences, 2024)
Among the most manufactured industrial organic chemicals are esters. They are widely used in a variety of household and commercial operations. This study was carried out using Fisher Esterification method to prepare the “Esters” from acids for the synthesis multiple flavors. The different flavors that have different physical properties were synthesized including: Scent of nail polish, spices, banana, pineapple flavor, oil, kiwi, purple flower, apple, pineapple, berries and grapes. Meanwhile, it was observed that when preparing ester flavors from liquid acids, they had a strong and clear smell compared to solid acids, which had a somewhat weak smell. من بين المواد الكيميائية العضوية الصناعية الأكثر تصنيعاً هي الإسترات. يتم استخدامها على نطاق واسع في مجموعة متنوعة من العمليات المنزلية والتجارية. أجريت هذه الدراسة باستخدام طريقة فيشر إسترة لإعداد "الإسترات" من الأحماض لتوليف نكهات متعددة. تم تصنيع النكهات المختلفة التي لها خصائص فيزيائية مختلفة بما في ذلك: رائحة طلاء الأظافر والتوابل والموز ونكهة الأناناس والزيت والكيوي والزهرة الأرجوانية والتفاح والأناناس والتوت والعنب. وفي الوقت نفسه، لوحظ أنه عند تحضير نكهات الإستر من الأحماض السائلة، كانت لها رائحة قوية وواضحة مقارنة بالأحماض الصلبة، التي كانت لها رائحة ضعيفة إلى حد ما